2022
DOI: 10.1101/2022.03.22.485379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why is the average collateral effect of synonymous mutations so similar across alternative reading frames?

Abstract: The standard genetic code has been shown to have multiple interesting properties which impact on molecular biology and the evolutionary process. One facet of molecular biology where code structure is particularly important is the origin and evolution of overlapping genes. We have previously reported that the structure of the standard genetic code ensures that synonymous mutations in a protein coding gene will lead to a remarkably similar average "collateral" mutation effect size in at least four out of the fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 92 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…It has similarly been suggested that there is a tendency for secondary structures found in the sense strand to be retained in antisense, in terms of the types of amino acids encoded (Zull and Smith 1990) and a tendency for conservative mutations in one strand to also be conservative in the other (Konecny et al 1993). This study of conservation in antisense has recently been extended to other frames, finding remarkable similarity across frames (Wichmann andArdern 2019, 2022).…”
Section: Antisense Codingmentioning
confidence: 89%
See 1 more Smart Citation
“…It has similarly been suggested that there is a tendency for secondary structures found in the sense strand to be retained in antisense, in terms of the types of amino acids encoded (Zull and Smith 1990) and a tendency for conservative mutations in one strand to also be conservative in the other (Konecny et al 1993). This study of conservation in antisense has recently been extended to other frames, finding remarkable similarity across frames (Wichmann andArdern 2019, 2022).…”
Section: Antisense Codingmentioning
confidence: 89%
“…Even synonymous mutations in a coding sequence in effect explore sequence space in alternative frames. The surprising similarity in this "collateral" effect size across alternative frames (Wichmann and Ardern 2019) may facilitate evolutionary exploration (Wichmann and Ardern 2022).…”
Section: Mechanisms Of Protein Novelty From Alternative Reading Framesmentioning
confidence: 99%